Use of Mini Solar Panels for Battery Charging in the Mini Robot Warehouse - Rizki Aulia Nanda; Karyadi Karyadi; Roban Roban (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Industrial businesses have employed various robot cars to execute tasks related to goods movement, such as the Warehouse Robot Car, which utilizes a line follower sensor system. However, the substantial electricity consumption poses a challenge due to excessive energy use in robot cars. In light of this issue, the research aims to assess the utilization of mini solar panels in robot cars equipped with 3.3V Li-ION 18650 batteries. The primary objective is to calculate the electricity required to operate a line-following robot car within the designated sector. The approach involves designing robotics and solar panel systems for generating input and output power, including charging measurements. According to the findings, solar panels can charge at a maximum rate of 0.206358 watts for 45 minutes, while the robot can operate at a minimum rate of 0.26 watts for 29 minutes, resulting in a charging efficiency to robot performance of 43.5 percents.